The Potential Role of BK and JC Polyomaviruses in Urothelial Cancer (Iraqi Journal of Medical Sciences, 2025)
Background:    BK and JC polyomaviruses are perceived as the two most common human polyomaviruses (HPyVs). These two viruses inhabit the epithelial surfaces of the bladder and kidney as the primary site of replication and latency. There have been multiple evidences on the association and implication of some of the HPyVs in human cancerous growth, indicating an etiological association with carcinogenesis.Objective:    To explore the association and implication of some of the polyomaviruses in urothelial carcinomas. Methods: Tissue biopsies were collected from 103 patients with urothelial carcinoma. The biopsies were processed for polyomavirus DNA and large T antigen (TAg) through real-time polymerase chain reaction (PCR) and immunohistochemistry (IHC).Results: BK polyomavirus and JC polyomavirus were detected in 21 cases (29.6%) and 10 cases (14.1%) with malignant tumors, respectively. The percentage of cases with double positive BK polyomavirus DNA and TAg was found to be high (62.20%). The specificity was high for both BK and JC viruses (98.48%).Conclusion: The study suggests that JC and BK polyomaviruses may play an important role in the urothelial tumor development. Keywords: Polyomavirus, HPyVs, urothelial cancer, BK virus, JC virus, tumors, Large T-Ag, real-time PCR, ImmunohistochemistryCitation: AlMalaki KA, Al-Obaidi AB, Ghazi HF. The potential role of BK and JC polyomaviruses in urothelial cancer. Iraqi JMS. 2025; 23(1): 17-24. doi: 10.22578/IJMS.23.1.2